2022
DOI: 10.1186/s12882-022-02779-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of glomerulotubular crosstalk genes mediating IgA nephropathy by integrated bioinformatics

Abstract: Background IgA nephropathy (IgAN), which has been reported as the most prevalent glomerulonephritis globally, is the major contributor to end-stage renal diseases. This bioinformatics study aimed to explore glomerulotubular crosstalk genes and dysregulated pathways relating to the pathogenesis of IgAN. Methods The microarray datasets from the Gene Expression Omnibus (GEO) database were searched. Weighted gene co-expression network analysis (WGCNA) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 43 CYBB has been proposed as a primary component of the microbicidal oxidase system of phagocytes. Recent studies have suggested its role in the pathogenesis of immunoglobulin A nephropathy 44 , 45 , though its role in AKI remains unclear. VCAN, a member of the aggrecan/versican proteoglycan family, is involved in cell adhesion, proliferation, migration, and angiogenesis, playing an essential role in tissue morphogenesis and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“… 43 CYBB has been proposed as a primary component of the microbicidal oxidase system of phagocytes. Recent studies have suggested its role in the pathogenesis of immunoglobulin A nephropathy 44 , 45 , though its role in AKI remains unclear. VCAN, a member of the aggrecan/versican proteoglycan family, is involved in cell adhesion, proliferation, migration, and angiogenesis, playing an essential role in tissue morphogenesis and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GO analysis for BP, the DEGs were statistically significantly associated with inflammatory, camp, and cellular responses to lipopolysaccharide, cytokine-mediated signaling pathway, and neutrophil chemotaxis. Among them, some previous studies found response to inflammatory 10 , 21 , 30 , response to camp 10 , 21 , 22 , 31 , and cellular response to lipopolysaccharide 10 , 21 as highly significant GO terms.…”
Section: Discussionmentioning
confidence: 99%